Community recovery and assistance following large wildfires: The case of the Carlton Complex Fire. (October 2017) - Edgeley, Catrin M.; Paveglio, Travis B.
Abstract: Existing hazards literature highlights a growing need to understand long-term community recovery following impactful wildfire events. More specifically, little research explores how local perspectives about agency suppression efforts or the allocation of disaster aid following a wildfire influence recovery processes or adaptive actions to prepare for future hazards. We conducted interviews with 87 professionals and local residents one year after the Carlton Complex Fire in north-central Washington, including 53 who had experienced some form of property damage. Evidence of both social conflict and cohesion were apparent during and after the fire. Some local residents and professionals were disappointed with fire management approaches that they felt were not aggressive enough. They also expressed frustration with a lack of Individual Assistance aid from FEMA (the Federal Emergency Management Agency), which they attributed to the challenging nature of the application process and lack of understanding about rural impacts from wildfires. Unmet expectations about recovery aid and skepticism about future firefighting efforts influenced recovery efforts focused on building local autonomy during future hazard events. Results from our work suggest that Volunteer Organizations Active in Disaster (VOADs) can help rural communities navigate aid and recovery processes. They also indicate a need for additional research on and documentation about the decision processes or criteria that residents used to assess social impact or recovery needs among rural communities that will be affected by future wildfires. Highlights: We interviewed 87 residents and professionals after the Carlton Complex Fire. Disagreements about suppression tactics led to distrust among locals and agencies. Interactions with government agencies and organizations influenced local recovery. Respondents felt that FEMA assistance was warranted given the scale of impacts. Wildfire events can interact with and modify perspectives about local adaptation.